Development and characterization of chromosome segment substitution lines derived from Oryza rufipogon in the genetic background of O. sativa spp. indica cultivar 9311. (December 2016) - Qiao, Weihua; Qi, Lan; Cheng, Zhijun; Su, Long; Li, Jing; Sun, Yan; Ren, Junfang; Zheng, Xiaoming; Yang, Qingwen
Abstract Background Wild rice (Oryza rufipogon ) constitutes a primary gene source for rice breed improvement. Chromosome segment substitution line (CSSL) forO. rufipogon is a powerful tool for fine mapping of quantitative traits, new gene discovery, and marker-assisted breeding. Thus, they provide a basis for a wide range of genomic and genetic studies. Results In this study, a set of 198 CSSLs were developed from a cross between recurrent parentindica var. 9311 and anO. rufipogon donor parent; these were then genotyped using 313 polymorphic SSR markers evenly distributed across the 12 rice chromosomes. On average, each CSSL carried 2.16 introgressed segments, and the genetic distance of each segment was about 6 cM. The segments collectively covered 84.9 % of the wild rice genome. Based on these CSSLs, 25 QTLs involved in 10 agronomic traits were identified. Seven CSSLs were subjected to a whole-genome single nucleotide polymorphism chip assay and two QTLs, qSH4-1 andqDTH10-1, detected. In addition, a new QTL associated with the heading date was detected in a 78-Kb region on chromosome 10, thus proving the ability of these CSSLs to identify new QTLs and genes. Conclusions The newly developed CSSL population proved a useful tool for both gene identification and whole-genome research of wild rice. These CSSL materials will provide a foundation for rice variety improvement.